Transference of a crystal protein gene from bacillus thuringiensis and its expression in bradyrhizobium sp. cells - Da Costa Lima, Paulo Sarmanho; Lemos, Manoel Victor Franco [UNESP]; Lemos, Eliana G. Macedo [UNESP]; Alves, Lúcia Maria Carareto [UNESP] (Springer Nature, 2000)
The plasmid pHT409 that harbours the cryIA(a) gene for the production of a δ-endotoxin (crystal protein) from Bacillus thuringiensis was transferred into Bradyrhizobium sp. A conjugal transfer system aiming to introduce the plasmid into the Bradyrhizobium sp. host from colonies of an Escherichia coli donor strain (DH5α
Keywords: Bacillus thuringiensis; Bradyrhizobium sp; Conjugation; cryIA (a); Crystal protein; Plasmid stability; crystal protein; gene transfer; genetic strain; plasmid